Effects Of Cymbopogonflexuosus Essential Oil And Ph On Anti-coagulant Activity Of Extracellular Proteins Secreted By Bacillus Subtilis ATCC21332 - Hairul Shahril Muhamad; Nabilah Ahmad Alhadi; Maryam Mohamed Rehan; Salina Mat Radzi; Hanina Mohd Noor (Department of Mathematics MC College, 2024)
Blood clotting is an emerging problem that seriously threatens the health of human beings such as strokes and heart attacks. For the treatment, anti-coagulants are used in which it could prevent and interrupt the process involved in the formation of blood clots. Microbial proteases have now been attracted since it is cost effective and no side effects than typical anti-coagulant agents. The protease enzymes were discovered from many microorganisms including Bacillus sp. Previous study reported that B. subtilis could produce a serine protease, known as Bacillopeptidase F with anti-coagulant activity. However, study on anti-coagulant activity of microbial protein secreted by B. subtilis after being induced with Cymbopogonflexuosus essential oil and cultured at difference pH media is still limited. In this present study, B. subtilis ATCC21332 cells were treated with a low concentration (0.01 MIC) of C. flexuosus essential oil and cultured in difference pH media (pH 6, pH 7 and pH 8) at 30°C for 72 h of fermentation. The extracellular proteins were then extracted and precipitated by using 80% of ammonium sulfate before being further identified using Sodium Dodecyl Sulfate-Polyacrylamide Gel Electrophoresis(SDS-PAGE) and tested for anti-coagulant activity. SDS-PAGE analysis exhibited a proteins profile with a band in approximate size of 30 kDa was appeared for the treated bacteria with C. flexuosus essential oil and cultivated at three difference pH of media. The extracellular proteins secreted by B. subtilis ATCC21332 after being treated with 0.01 MIC of C. flexuosus essential oil and cultivated either at pH 6 or pH 7 or pH 8 could also prevent blood clotting. However, the extracellular proteins produced by B. subtilis ATCC21332 without inducing with 0.01 MIC of C. flexuosus essential oil only exhibited anti-coagulant activity when the bacterial cells were cultured at pH 7. As a conclusion, B. subtilis ATCC21332 can be enhanced to produce anti-coagulant enzymes aftern being treated with low concentration of C. flexuosus essential oil and cultivated in natural pH media or even in slightly basic or slightly acidic environment. Further study should be done to purify, identify and analyze the anti-coagulant enzymes from B. subtilis ATCC21332.